Relationship between Perceived Paternal Care and Depressive Symptoms among Adolescent Boys in Kiambu County - Kuboka, Venoranda Rebecca; Gitonga, Dr. Ciriaka (Journal of Advanced Psychology, 2020)
Purpose: Perceived paternal care is attributed to the development of depression among adolescents. Depression is characterized by moodiness, low interest in activities, acting out and aggressiveness. This study examined the relationship between perceived paternal care and development of depression among adolescent boys in selected secondary schools in Kiambu County, Kenya. In Kenya, few studies have been done to examine how paternal care predicts the development of depression among adolescent boy in Kenya. Many studies have examined how parenting styles contribute to depression in the context of both parents, that is, the mother and father. Few studies seem to focus on assessing how paternal care predicts the development of depression among boys in Kenya. Methodology: Spearman Rank Correlation was used to test the relationship between paternal care and development of depression. Stratified random sampling was used to select four boy's schools. Purposive sampling was then used to select 87 boys who had fathers. Perceived parental care was assessed using the paternal nurturance scale. Depression scale was assessed using the Center Epidemiological Studies Depression Scale for Children (CES-DC). Results: The study findings revealed that there is a negative correlation of (r= -.239) between perceived paternal care and depression among adolescent boys. Contribution: The findings of the study will help mental health practitioners to develop interventions that incorporate parents in addressing the psychological needs of adolescents.